2007
DOI: 10.1111/j.1365-294x.2007.03241.x
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic consequences of geographic disjunction: a prairie plant isolated on Great Lakes alvars

Abstract: Species may often exhibit geographic variation in population genetic structure due to contemporary and historical variation in population size and gene flow. Here, we test the predictions that populations on the margins of a species' distribution contain less genetic variation and are more differentiated than populations towards the core of the range by comparing patterns of genetic variation at five microsatellite loci between disjunct and core populations of the perennial, allohexaploid herb Geum triflorum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 64 publications
3
73
0
Order By: Relevance
“…Although the study of neutral genetic diversity in polyploids can be complicated by genotype ambiguity (Clark and Jasieniuk, 2011), recently developed methods have proven useful in estimating genetic diversity and how it is structured geographically (for example, Hamilton and Eckert, 2007;Marrs et al, 2008). Here, we found very congruent patterns of genetic diversity and structure between different methods.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Although the study of neutral genetic diversity in polyploids can be complicated by genotype ambiguity (Clark and Jasieniuk, 2011), recently developed methods have proven useful in estimating genetic diversity and how it is structured geographically (for example, Hamilton and Eckert, 2007;Marrs et al, 2008). Here, we found very congruent patterns of genetic diversity and structure between different methods.…”
Section: Discussionsupporting
confidence: 61%
“…Because allele and genotype frequencies cannot be estimated, it is not possible to use classical diversity and structure statistics, such as H and F ST . Instead we used phenotype-based methods recently developed for polyploids (Obbard et al, 2006;Falush et al, 2007) that have proven useful in comparing genetic diversity and genetic structure at microsatellite loci between regions in plant species (for example, Hamilton and Eckert, 2007;Marrs et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…and Lake Huron Tansy (Tanacetum huronense Nutt. ), suggests that this region represents the likely original site of entry for C. pitcheri as well as other dune endemics (Guire and Voss, 1963;Hannan and Orick, 2000;Hamilton and Eckert, 2007). The mosaic pattern of genetic diversity would indicate that colonization has been sporadic, particularly toward the south, with rare and erratic long-distance dispersal events (Cruzan and Templeton, 2000;Clark, 1998) associated with habitat preference having an important role .…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, some (but not all) individual studies have shown greater intraspecific genetic variation in larger [3,[11][12][13][14][15], denser [16], or less-isolated [17][18][19][20] populations. Other patterns include lower genetic variation in degraded and logged habitats [21], clines in allele frequencies [22,23] discontinuities among geographically-separated portions of the range [18,24] or between organisms separated by landscape barriers [25], higher variation in unglaciated portions of species' ranges [26], higher genetic variation in core versus marginal populations [27][28][29][30], and differences in genetic variation between distinct habitats (prairie versus alvar) [31]. Studies considering the effects of original habitat patch size, current patch size, population area, and areas of nearby suitable habitat within the landscape on local genetic variation are less common but also show positive relationships [32,33].…”
Section: Introductionmentioning
confidence: 99%